Tectonic segmentation across Patagonia controlled by the subduction of oceanic fracture zones. (January 2021) - Orts, Darío Leandro; Álvarez, Orlando; Zaffarana, Claudia; Gimenez, Mario; Ruiz, Francisco; Folguera, Andrés
Graphical abstract: Highlights: Relief anomalies coincide with the location of the subducting oceanic fracture zones. Vertical gravity gradients allow identifying structures related to ENE lineaments. Crustal-scale segmentation is recognized at distances > 500 km from the trench. Coupling zone heterogeneity implies lateral variations in deformational patterns. Abstract: A set of fracture zones left by transform faults segmenting the active Chile Ridge that separates the Nazca and Antarctica Plates has been subducting beneath western Patagonia in the last 18 Myr. The subduction direction of these fractures zones has remained almost unaltered during this time lapse since these intersected the Chilean trench. In this context, the analyzed Patagonian sector is associated with the subduction of a highly buoyant oceanic floor due to its relatively young age that contrasts with the ocean floor bathymetry to the north where oceanic crust gets progressively older up to the Eocene and consequently isostatically subsides. Short-term elastic deformational patterns associated with the earthquake cycle have been linked to this segmentation imposed by subducting fracture zones in previous works. Similarly, this work explores the relationship between long-term topography, seismicity, gravity, and magnetic anomalies as a proxy for upper crustal structure, deformation, exhumation, and consequently surface geology segmented nature associated with this pattern of oceanic fracture zones. Through these analyses, we have identified a series of ENE structural trends or lineaments across the continental crust that could be directly related to the segmented mechanical behavior of the plate interface and enhanced by particular climatic and tectonic history of the Patagonian region. These evidences could contribute to the understanding of how fracture zones can control, to a certain extent, the segmented nature of the upper plate in a subduction setting.